2014
DOI: 10.3109/14992027.2014.880813
|View full text |Cite
|
Sign up to set email alerts
|

Bone conduction hearing sensitivity in normal-hearing subjects: Transcutaneous stimulation at BAHA vs BCI position

Abstract: It was found that both the objective ECSP and the subjective hearing threshold measurements gave similar improvement as previous LDV measurements for stimulation closer to the cochlea. One exception was that the LDV measurements did not show the improved sensitivity for frequencies below 500 Hz found here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
(18 reference statements)
2
17
0
Order By: Relevance
“…The audiometric results of the first patient at the 1-month follow-up are published by Eeg-Olofsson et al 49 and the first six patients’ 6-month follow-up by Reinfeldt et al 50 Before the clinical study, preclinical studies were performed on cadavers, 51 54 dry skulls, 55 animals, 56 , 57 and normal-hearing subjects. 58 In the important preclinical studies on the cadavers, 51 , 52 where it was first concluded that an active transcutaneous BCD could be a realistic alternative to a percutaneous system, the sound processor and induction link from the Vibrant Soundbridge (the study was supported by MED-EL) was used to drive a BEST transducer. One important finding in these investigations was that MPO in the transcutaneous solution was considered high enough compared with a percutaneous BAHA solution, which most likely triggered the work to develop complete active transcutaneous systems like the BCI and the Bonebridge™ systems.…”
Section: Bone-conduction Devicesmentioning
confidence: 99%
“…The audiometric results of the first patient at the 1-month follow-up are published by Eeg-Olofsson et al 49 and the first six patients’ 6-month follow-up by Reinfeldt et al 50 Before the clinical study, preclinical studies were performed on cadavers, 51 54 dry skulls, 55 animals, 56 , 57 and normal-hearing subjects. 58 In the important preclinical studies on the cadavers, 51 , 52 where it was first concluded that an active transcutaneous BCD could be a realistic alternative to a percutaneous system, the sound processor and induction link from the Vibrant Soundbridge (the study was supported by MED-EL) was used to drive a BEST transducer. One important finding in these investigations was that MPO in the transcutaneous solution was considered high enough compared with a percutaneous BAHA solution, which most likely triggered the work to develop complete active transcutaneous systems like the BCI and the Bonebridge™ systems.…”
Section: Bone-conduction Devicesmentioning
confidence: 99%
“…In general 5‐ to 15‐dB improvement in cochlear sensitivity at frequencies above 1 kHz can be expected when a BC transducer is attached directly to the skull . Generally, the closer the stimulation position is to the cochlea, the greater the stimulation of the cochlea and the hearing thresholds …”
mentioning
confidence: 99%
“…For the BCI, the skin and subcutaneous tissues are kept intact and no screw attachment to the skull bone is needed. Moreover, the BCI transducer is implanted closer to the cochlea than a BAHA, which increases the ipsilateral sensitivity to bone-conducted sound (Håkansson et al, 2008(Håkansson et al, , 2010Stenfelt et al, 2000;Stenfelt & Goode, 2005b;Eeg-Olofsson et al, 2008;Reinfeldt et al, 2014).…”
Section: The Bone Conduction Implantmentioning
confidence: 99%